KAJIAN PENGEMBANGAN KLASTER KOMODITAS BAWANG MERAH DI KANTOR PERWAKILAN BANK INDONESIA TEGAL - Solekha, Anis; Widianto, Andri; Karunia, Anita (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2020)
Bank Indonesia (BI) is the Central Bank of the Republic of Indonesia which is responsible for achieving and maintaining the stability of the rupiah value, such as maintaining the stability of volatile food. Volatile food can be maintain using cluster development, one of them is the shallot commodity cluster. This study aimed to determine the development of shallot commodity clusters in the context of controlling inflation at the Tegal Bank Indonesia Representative Office. Data collection techniques used were observation, interviews, and literature study. The data analysis technique used is descriptive qualitative analysis through a fishbone diagram instrument. The results of the fishbone diagram analysis showed the factors that influence the shallot commodity on inflation control in Brebes Regency are farmers, upstream factors, environmental factors, and downstream factors. Shallot is the main contributor to inflation in Brebes district, in 2016 these commodities contributed to inflation by 0.33%, in 2017-2019 commodities contributed to deflation of -0.26%, -0.22274% and -0.0883%. The conclusion is the development of shallot commodity cluster in the context of controlling inflation in the Tegal Bank Indonesia Representative Office using a fishbone diagram instrument considered to be good enough.